Entitled to Property: How Breaking the Gender Barrier Improves Child Health in India - Md Shahadath Hossain; Plamen Nikolov (Institute of Labor Economics (IZA), 2023)
Non-unitary household models suggest that enhancing women's bargaining power can influence child health, a crucial determinant of human capital and economic standing throughout adulthood. We examine the effects of a policy shift, the Hindu Succession Act Amendment (HSAA), which granted inheritance rights to unmarried women in India, on child health. Our findings indicate that the HSAA improved children's height and weight. Furthermore, we uncover evidence supporting a mechanism whereby the policy bolstered women's intra-household bargaining power, resulting in downstream benefits through enhanced parental care for children and improved child health. These results emphasize that children fare better when mothers control a larger share of family resources. Policies empowering women can yield additional positive externalities for children's human capital
Keywords: D13; I12; I13; J13; J16; J18; K13; O12; O15; Z12; Z13; 330; human capital; height; bargaining; parental investments; developing countries; India